Development of Cooperative Learning Tools Type Course Review Horay and Geogebra Media to Improve Spatial Thinking Skills and Mathematical Resilience of Grade VIII Students - Siregar, Putri Mayang Sari; Syahputra, Hermawan; Fauzi, KMS. Amin (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This study aims to investigate the improvement and development of spatial thinking skills and mathematical resilience abilities of students using cooperatively developed learning tools of the Course Review Horay and Media Geogebra type; to investigate the validity, practicability, and efficacy of cooperatively developed learning tools of the Course Review Horay and Media Geogebra type in enhancing spatial thinking skills and resilience. This type of research is development research based on the ADDIE model. 33 MTs Al-Washliyah Tembung students participated in the study. The results demonstrated that 97% of the students, or 32 out of 33, improved their spatial reasoning skills. While only 19 of 33 students, or 58%, exhibited an increase in mathematical resilience. In addition, the results indicate that this development model is more effective than conventional classroom learning models at enhancing spatial reasoning and mathematical resilience. The learning aids created using cooperative Course Review Horay type and Geogebra are valid, applicable, and efficient.Keywords: ADDIE, Spatial Thinking Skills, Mathematical Resilience, Development Research